2018
DOI: 10.1080/09593985.2018.1425512
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of pain experiences and their meaning in people with chronic obstructive pulmonary disease

Abstract: Patients report difficulty in explaining the persistence of pain. This fosters a need to legitimize their pain, which influences feelings of frustration and self-worth. An understanding of these responses will assist health care professionals in managing on-going pain in those with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…6 Recently, Lee et al reported similar results on the negative interaction between several symptoms and pain. 7…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Recently, Lee et al reported similar results on the negative interaction between several symptoms and pain. 7…”
Section: Introductionmentioning
confidence: 99%
“…Pain in COPD is also associated with diminished physical activity and lower functional exercise capacity, 8,9 often worsened by pain-related fear of movement. 4,7 The relationship between pain, symptoms and physical activity is important, since lifelong adherence to physical activity is essential to improve HRQoL and prognosis in COPD.…”
Section: Introductionmentioning
confidence: 99%
“…44 46 47 Psychological reactions to pain (anger, fear, frustration, depression) were also described in our study as well as previous studies as people talked about how pain overwhelmed or frightened them or negatively impacted their mood, leaving them frustrated, aggravated, depressed or hypervigilant. [25][26][27][28] This suggests that people are able to convey how they physically and psychologically react to pain without the need for an independent observer to be present in the moment pain is being experienced.…”
Section: Discussionmentioning
confidence: 99%
“…11 Previous qualitative research in other diagnoses has investigated more deeply how pain is experienced and expressed and how it interferes with one's life. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] One of the problems inherent in how we respond clinically to pain is that when pain is assessed it is often measured, with a focus on pain intensity using quantitative scales. 23 However, there is an indication that patients use different approaches when rating pain intensity on scales such as the Brief Pain Inventory (BPI), which includes considering how pain fluctuates as well as the location and duration of the pain.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the stated inability of van Dam van Isselt et al (2014) to identify a single study reporting a specific intervention strategy to manage pain in people with COPD [3], we also failed to identify such studies. However, the rehabilitation community is clearly working towards this through the confirmation of appropriate pain assessment instruments [86] and qualitative explorations of the pain experiences in people with COPD in order to develop a pain management program specific to this population [87,88].…”
Section: Discussionmentioning
confidence: 99%